Item analysis of pre-service EFL teachers' formative test in teaching practicum for program evaluation - Hartati, Neti (LingTera, 2024)
Teaching practicum is crucial for pre-service EFL teachers' professional development. Many studies have investigated student-teachers' performance in teaching practicum in various aspects. However, research on their performance in constructing test items in teaching practicum has not been found. Test construction is an essential pedagogical competence that student-teachers must master. Investigating their performance in test construction may give valuable feedback to student-teachers and for teacher education. To fill the research gap, this study conducted an item analysis of a formative test constructed by two student-teachers in a teaching practicum. It revealed that the DP of the items have good quality but the FV analysis showed there is no difficult item suggesting that they cannot make difficult questions. The test reliability is high (0.900625) but there are 6 invalid items. Three items contain grammatical errors creating students' confusion influencing the FV, DP, and the validity. It revealed that the test makers' grammar mastery may determine item quality. It suggests student-teachers improve their grammar mastery, and teacher education improves the quality of English grammar teaching and refine their curriculum of evaluation and language testing subjects and include the evaluation of student-teachers' performance in language assessment in teaching practicum program as a focus.